2021
DOI: 10.3390/jcm10245735
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of the Development of Protracted Bacterial Bronchitis following Presentation to Healthcare for an Acute Respiratory Illness with Cough: Analysis of Three Cohort Studies

Abstract: We describe the prevalence and risk factors for protracted bacterial bronchitis (PBB) following healthcare presentation for an acute cough illness in children. Data from three studies of the development of chronic cough (CC) in children were combined. PBB was defined as a wet cough of at least 4-weeks duration with no identified specific cause of cough that resolved following 2–4 weeks of appropriate antibiotics. Anterior nasal swabs were tested for 17 viruses and bacteria by polymerase chain reaction. The stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 44 publications
(77 reference statements)
0
10
0
1
Order By: Relevance
“… 81 Childcare attendance, prior history of chronic cough and age < 2 years increased the risk of PBB following the healthcare presentation for an acute cough illness in children, while a baseline diagnosis of asthma/reactive airways disease or bronchiolitis decreased the risk. 81 Clinicians and parents should be aware of the risk factors and symptoms for PBB. Such knowledge and health‐seeking behaviour can be improved through education with culturally secure health information.…”
Section: Other Respiratory Infectionsmentioning
confidence: 98%
See 3 more Smart Citations
“… 81 Childcare attendance, prior history of chronic cough and age < 2 years increased the risk of PBB following the healthcare presentation for an acute cough illness in children, while a baseline diagnosis of asthma/reactive airways disease or bronchiolitis decreased the risk. 81 Clinicians and parents should be aware of the risk factors and symptoms for PBB. Such knowledge and health‐seeking behaviour can be improved through education with culturally secure health information.…”
Section: Other Respiratory Infectionsmentioning
confidence: 98%
“…Protracted bacterial bronchitis (PBB) is a common cause of chronic productive cough in childhood. It is defined as a wet cough of at least 4‐week duration with no identified specific cause of cough that resolved following 2–4 weeks of appropriate antibiotics 81 . Childcare attendance, prior history of chronic cough and age < 2 years increased the risk of PBB following the healthcare presentation for an acute cough illness in children, while a baseline diagnosis of asthma/reactive airways disease or bronchiolitis decreased the risk 81 .…”
Section: Other Respiratory Infectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study (35) that recruited 903 children presenting with acute cough and followed-up for development of chronic cough found that the risk factors for PBB were: childcare attendance [adjusted relative risk (aRR) = 2.32, 95% CI 1.48-3.63], prior history of chronic cough (aRR = 2.63, 95% CI 1.72-4.01), and age <2-years (<12-months: aRR = 4.31, 95% CI 1.42-13.10; 12-<24 months: aRR = 2.00, 95% CI 1.35-2.96). Factors that decreased the risk were baseline diagnoses of asthma/reactive airway disease (aRR = 0.30, 95% CI 0.26-0.35) or bronchiolitis (aRR = 0.15, 95% CI 0.06-0.38) (35).…”
Section: Pre-school Childrenmentioning
confidence: 99%